Il ruolo dell’informazione nell’accettazione di novel food da parte del consumatore: il caso della carne coltivata (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Meat grown in labs, also known as cultured meat, is currently under development and will likely soon be available on supermarkets’ shelves. Such new meat-based products may tackle some of the most controversial societal concerns related to the industry, in particular animal wellbeing and environmental impacts, with further potential improvements concerning food security. However, due to its high degree of novelty, it remains unclear how consumers view this type of food product. The present study aims at unveiling the perception, acceptance, and willingness to try, buy, and pay a premium price for cultured meat in the Italian context, deconvoluting the effect of providing positive information to consumers.
Keywords: Cultured meat; information; consumer perception; novel food; in vitro meat